2016
DOI: 10.1016/j.physa.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in directed networks

Abstract: Reciprocity is an important characteristic of directed networks and has been widely used in the modeling of World Wide Web, email, social, and other complex networks. In this paper, we take a statistical physics point of view and study the limiting entropy and free energy densities from the microcanonical ensemble, the canonical ensemble, and the grand canonical ensemble whose sufficient statistics are given by edge and reciprocal densities. The sparse case is also studied for the grand canonical ensemble. Ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…In some other cases, it may be possible to get approximate analytic solutions using a variety of techniques (mean-field theory, saddle-point approximation, diagrammatic perturbation theory, path integral representations). These situations have been vastly explored in the literature, and include the degree-correlated network model [115], the reciprocity model and the two-star model [116,117], the Strauss model of clustering [118], models of social collaboration [119], models of community structure [31], hierarchical topologies [120], models with spatial embedding [121] and rich-club features [122], and finally model constraining both the degree distribution and degree-degree correlations-which are known under the name of Tailored Random Graphs [123][124][125]. At last, when any analytic approach for computing Z becomes intractable, the ensemble can be still populated using Monte Carlo simulations, either to explicitly sample the configuration space-taking care of avoiding sampling biases through the use of ergodic Markov chains fulfilling detailed balance [126][127][128], or to derive approximate maximum likelihood estimators-taking care of avoiding degenerate regions of the phase space leading to frequent trapping in local minima [129][130][131][132][133][134][135].…”
Section: Beyond Local Constraintsmentioning
confidence: 99%
“…In some other cases, it may be possible to get approximate analytic solutions using a variety of techniques (mean-field theory, saddle-point approximation, diagrammatic perturbation theory, path integral representations). These situations have been vastly explored in the literature, and include the degree-correlated network model [115], the reciprocity model and the two-star model [116,117], the Strauss model of clustering [118], models of social collaboration [119], models of community structure [31], hierarchical topologies [120], models with spatial embedding [121] and rich-club features [122], and finally model constraining both the degree distribution and degree-degree correlations-which are known under the name of Tailored Random Graphs [123][124][125]. At last, when any analytic approach for computing Z becomes intractable, the ensemble can be still populated using Monte Carlo simulations, either to explicitly sample the configuration space-taking care of avoiding sampling biases through the use of ergodic Markov chains fulfilling detailed balance [126][127][128], or to derive approximate maximum likelihood estimators-taking care of avoiding degenerate regions of the phase space leading to frequent trapping in local minima [129][130][131][132][133][134][135].…”
Section: Beyond Local Constraintsmentioning
confidence: 99%
“…A large number of scholars have focused on the integration of exogenous mechanisms and endogenous structures of trade networks. Generally, reciprocal behavior is an important tendency in social relations, where countries in trade networks trade with other countries based on the theory of comparative advantage and reciprocity [ 35 , 36 ]. In addition, triangular structure (transitivity) is also considered a fundamental building block in international trade networks.…”
Section: Theoretical Framework and Assumptionsmentioning
confidence: 99%
“…Reciprocity is an important feature of directed networks that explains the relationships formed by nodes through feedback. Reciprocity is a measure of the simplest interaction processes occurring in the network and is widely used when modeling complex networks [53]. Garlaschelli and Loffredo [54] found that the detection of reciprocity helps reveal the formation mechanisms of the observed network topology and explain its organization principles.…”
Section: Structure-dependent Effectsmentioning
confidence: 99%